Ground-state β-feeding determination using total-absorption spectrometers - Guadilla, Víctor (Frontiers in Physics, 2024)
The determination of the β intensity probability between the ground states of parent and daughter nuclei has traditionally been a difficult task with standard γ-spectroscopy approaches, due to the lack of the associated γ emission. In the last years, the total absorption γ-ray spectroscopy technique has successfully proven its ability to deal with this problem by means of different procedures. In this article I discuss the potential of these methods and a new approach for segmented total absorption γ-ray spectrometers will also be introduced. An overview of applications will be presented based on past, present and future β-decay experiments.